Can the Distributional Impacts of Macroeconomic Shocks be Predicted? A Comparison of the Performance of Macro-Micro Models with Historical Data for Brazil - Ferreira, Francisco H.G.; Leite, Phillippe George; Pereira da Silva, Luiz A.; Picchetti, Paulo (World Bank, Washington, D.C., 2013)
What was the impact of Brazil's 1998-99 currency crisis-which resulted in a change of exchange rate regime and a large real devaluation-on the occupational structure of the labor force and the distribution of incomes? Would it have been possible to predict such effects ahead of the crisis? The authors present an integrated macro-micro model of the Brazilian economy in 1998. The model consists of an applied general equilibrium macroeconometric component, connected through a set of linkage aggregate variables to a microeconomic model of household incomes. The authors use this framework to predict the employment and distributional consequences of the 1999 Brazilian currency crisis, based on 1998 household survey data. They then test the predictive performance of the model by comparing its simulated results with the actual household survey data observed in 1999. In addition to the fully integrated macro-micro model, the authors also test the performances of the microeconometric model on its own, and of a "representative household groups" approach. They find that the integrated macro-micro econometric model, while still inaccurate on many dimensions, can actually predict the broad pattern of the incidence of changes in household incomes across the distribution reasonably well, and much better than the alternative approaches. The authors conclude that further experimentation with these tools might be of considerable potential usefulness to policymakers.